Fabrication, characterization, antihypertensive effect and potential mechanisms of a novel angiotensin Ⅰ-converting enzyme inhibitory peptide derived from garlic by-products - Xiang Lu; Zhenjia Zheng; Yongqiu Qi; Haihua Chen; Zhichang Qiu; Xuguang Qiao (Food Science and Human Wellness)
The valorization of vegetable by-products is a promising strategy to combat climate change and achieve global carbon neutrality goals. This study aimed to exploit the high-value utilization of garlic by-products and to investigate the antihypertensive effects and potential mechanisms of the resulting angiotensin Ⅰ-converting enzyme (ACE) inhibitory peptides. After protein extraction, enzymatic hydrolysis, and activity-directed fractionation, a potent and highly stable ACE inhibitory peptide (IC50: 31.38 μmol/L) was obtained, which was identified as VWAS and acted as a competitive inhibitor. VWAS stably bound to key residues in the ACE active center mainly through hydrogen bonding interactions and effectively lowered blood pressure in spontaneously hypertensive rats via alleviating renal and cardiac injuries, improving endothelial dysfunction, and regulating the renal renin-angiotensin system, antioxidant system, and anti-inflammatory system. These findings suggested that garlic protein-derived peptide (VWAS) was a desirable candidate for antihypertensive functional foods and provided guidance for the high-value utilization of garlic by-products.